Numerical simulations of ductile fracture in steel angle tension members connected with bolts - Bernatowska, Edyta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to verify and present methodology for ultimate tensile resistance prediction in steel angle tension members connected to gusset plates with one row of bolts. After a description of the experimental investigations, the next step was to build numerical models.
Keywords: steel angle; bolted connections; tensile resistance; finite element modelling; Gurson-Tvergaard-Needleman material model; elementy stalowe; połączenia śrubowe; wytrzymałość na rozciąganie; modelowanie elementów skończonych; model materiałowy Gurson-Tvergaard-Needleman